Mapping Social Support and Barriers in Adaptive Sports: Bibliometric Implications for Inclusive Physical Education (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study provided a structured bibliometric mapping of research on social support and participation barriers in adaptive sports for athletes with disabilities and examined its implications for inclusive physical education. A bibliometric analysis was conducted using the Scopus database, covering publications from 2015 to 2025. A systematic search was conducted on 31 December 2025, identifying 142 documents, of which 71 peer-reviewed, English-language journal articles met the inclusion criteria and were analyzed following the PRISMA protocol. VOS viewer was employed to analyze publication trends, country contributions, collaboration networks, citation structures, and keyword co-occurrence patterns. Findings indicated a substantial increase in publication output since 2022, peaking in 2025 with 24 articles. Research production was concentrated in Europe and North America, led by Spain (10 publications), the United Kingdom (9), and the United States (8). Four major thematic clusters were identified, including psychosocial aspects and quality of life, social support and psychological factors, structural barriers and participation inclusivity, and clinical and rehabilitative approaches. The analysis revealed a fragmented knowledge structure, with limited integration between psychosocial and structural dimensions. This study advances the field by explicitly mapping their intersection and proposing integrative, policy-oriented directions to strengthen inclusive physical education.